2009
DOI: 10.1128/iai.01370-08
|View full text |Cite
|
Sign up to set email alerts
|

Major Surface Protein LipL32 Is Not Required for Either Acute or Chronic Infection with Leptospira interrogans

Abstract: Leptospira interrogans is responsible for leptospirosis, a zoonosis of worldwide distribution. LipL32 is the major outer membrane protein of pathogenic leptospires, accounting for up to 75% of total outer membrane protein. In recent times LipL32 has become the focus of intense study because of its surface location, dominance in the host immune response, and conservation among pathogenic species. In this study, an lipL32 mutant was constructed in L. interrogans using transposon mutagenesis. The lipL32 mutant ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
93
2
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(110 citation statements)
references
References 32 publications
6
93
2
9
Order By: Relevance
“…An extracellular matrix-binding assay was conducted as described previously (7,15). In brief, quadruplicate wells of a microtiter tray were incubated at 4°C overnight with 100 ml of a 500-g/ml solution of the extracellular matrix-like compound Matrigel (BD Biosciences) in phosphate-buffered saline and washed, and then a known quantity of bacteria was added.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An extracellular matrix-binding assay was conducted as described previously (7,15). In brief, quadruplicate wells of a microtiter tray were incubated at 4°C overnight with 100 ml of a 500-g/ml solution of the extracellular matrix-like compound Matrigel (BD Biosciences) in phosphate-buffered saline and washed, and then a known quantity of bacteria was added.…”
Section: Methodsmentioning
confidence: 99%
“…This is currently the only efficient means for constructing defined leptospiral mutants. This method has been applied for widespread random mutagenesis of the bacterial chromosome (13), facilitating the identification of two virulence factors (14,17) and the unexpected finding that the major outer membrane protein (LipL32) is not required for pathogenesis (15).…”
mentioning
confidence: 99%
“…LipL32 genes encode a lipoprotein that can be used as an adhesion molecule to laminin-collagens and fibronectin bands (15)(16)(17). LipL32 lipoprotein is a major outer membrane protein of Leptospira, which can only be found in pathogenic strains and absent in saprophytic bacteria (3,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Genome sequencing analyses have shown that saprophytic strains of Leptospira do not harbor genes orthologous to LipL32 (4), suggesting an important role of this protein in leptospiral pathogenesis. Although a knock-out of the lipL32 gene in pathogenic Leptospira did not prevent colonization of the renal tubules in a rat model of chronic infection (5), it is important to keep in mind that animal models may not reproduce all relevant conditions of infection and colonization in the host. Therefore, the precise role of LipL32 in Leptospira biology remains unclear.…”
mentioning
confidence: 99%